Lupus Pneumonitis Therapy Masks Coronavirus (COVID-19) - Soloway, S.; DePace, N. L.; Soloway, A. M.; Colombo, J. (Case Reports in Rheumatology, 2021)
Introduction. Coronavirus pneumonitis can mimic, or present as, lupus pneumonitis. Lupus may cause inflammation of the myocardium. Lupus pneumonitis high-dose steroid therapy may mask coronavirus (COVID-19). Case Study. The patient is a 65 y/o Hispanic female with lupus pneumonitis complicated by COVID-19. Her diagnosis was confirmed by a renal biopsy. She had nephritic and nephrotic syndrome. She was hospitalized a month earlier with shortness of breath with pulmonary infiltrates and was treated with steroids. The symptoms resolved quickly with shrinking consolidations and infiltrates. The patient returned to the office for shortness of breath with a presumptive diagnosis of recurrent lupus pneumonitis from steroid taper. The patient had a CT scan of the chest that revealed upper lobe interstitial and peripheral infiltrates. The radiologist felt that this was suspicious for coronavirus pneumonitis, and the patient was placed in isolation and continued therapy for lupus pneumonitis. She deteriorated, became hypoxic, and ventilated. Conclusion. All lupus pneumonitis patients, in fact all lupus patients in general (personal experience), on high-dose steroid therapy should be tested for COVID-19 to ensure proper diagnosis and therapy planning.